Hazard Identification and Risk Assessment (HIRA) Sebagai Upaya Mengurangi Risiko Kecelakaan Kerja dan Risiko Penyakit Akibat Kerja di Bagian Produksi PT. Iskandar Indah Printing Textile Surakarta - Ariani, Anisa Rahmadiana, Tarwaka, PGDip Sc, M.Erg, Sri Darnoto, SKM, M.PH (2016)
Occupational accidents high rates indicate the existention of awarenessless of the labors either the company regarding health safety issue, therefore accident measurement of risk by hazard identification is needed. The purpose of the research is to analyze the hazard possibility at PT. Iskandar Indah Printing Textile Surakarta production area using HIRA method. This research is descriptive observational. The object of this descriptive observational research are machine, attitude or behavior of labor, work process and work production environment such as winding, warping, sizing, ricing, weaving, inspecting, and folding. The result of identification shows there were 44 sources of danger, 8 as high levels category (18,2%), 19 medium levels category (43,2%), and 17 low levels category (38,6%). Based on this research, it can be concluded that the factors which caused a potential sources of danger are: unsafe working environment, the unsafe machine and unsafe working attitude. Based on this result, the researcher suggestes the company to immediately take significant action against any potential source of danger, especially at the high levels and the medium levels. Keywords : Hazard identification and risk assessment, unsafe working, diseases of work, textile